Development of cost functions for wastewater treatment by sequential batch reactor - Bhaskar Sengupta; Abhisek Roy; Somnath Mukherjee (Journal of Environmental Engineering and Landscape Management)
Sequential batch reactor is widely used for industrial wastewater treatment. To consider sequential batch reactor for biological treatment of wastewater at a specific site, it is essential to ensure economy and sustainability. An approach for scrutiny of economic aspects may be based upon use of cost functions to compare sequential batch reactor and other technologies. Such approach will enable to conduct prudent analysis and select the most economic treatment scheme for a particular project. In most of published studies, the cost functions for conventional wastewater treatment systems are described with historic or some other data available to the investigators. No detailed engineering exercise related to cost functions for sequential batch reactor is cited in earlier research studies. In this document the novel and appropriate methodology has been presented to develop cost functions based on engineering, estimation and statistical approach to forecast cost for sequential batch reactor based wastewater treatment system.